Cost-utility analysis of extensile lateral approach versus sinus tarsi approach in Sanders type II/III calcaneus fractures - Zihua Li; Xinbo Wu; Haichao Zhou; Shaochen Xu; Fajiao Xiao; Hui Huang; Yunfeng Yang (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background Extensile lateral approach had been recognized as the gold standard technique for displaced intra-articular calcaneus fractures (DIACFs) while sinus tarsi approach had been increasingly valued by surgeons and comparative clinical outcome was shown in both techniques. Appropriate decisions could be made by the clinicians with the help of cost-utility analysis (CUA) about optimal healthcare for type II/III calcaneus fracture. Method A single-center, retrospective study was conducted in which basic characteristics, clinical outcomes, and health care costs of 109 patients had been obtained and analyzed. Changes in health-related quality of life (HRQoL) scores, validated by EuroQol five-dimensional-three levels (EQ-5D-3L), were used to enumerate quality-adjusted life years (QALYs). Cost-effectiveness was determined by the incremental cost per QALY. Results One hundred nine patients were enrolled in our study including 62 in the ELA group and 47 in the STA group. There were no significant differences between these two groups in mean total cost, laboratory, and radiographic evaluation expense, surgery, anesthesia, and antibiotic expense. The expense of internal fixation materials ($3289.0 ± 543.9) versus ($2630.6 ± 763.7) and analgesia ($145.8 ± 85.6) versus ($102.9 ± 62.7) in ELA group were significantly higher than in the STA group (P < .001, P = .008, respectively). Visual Analogue Scale (VAS) scores showed significant difference at postoperative 3 and 5 days (P < .001). American Orthopaedic Foot and Ankle Society (AOFAS) ankle-hindfoot scores and the Bohlers’ and Gissane angle showed no significant differences between the two groups before and after the operation. The cost-effectiveness ratios of ELA and STA were $8766.8 ± 2835.2/QALY and $7914.9 ± 1822.0/QALY respectively, and incremental cost-effectiveness ratio (ICERs) of ELA over STA was $32110.00/QALY, but both showed no significant difference. Conclusion Both ELA and STA techniques are effective operative procedures for the patients with calcaneus fracture. Moreover, STA seems to be more reasonable for its merits including less postoperative pain, and less expense of analgesia as well as internal fixation materials. Level of evidence 5